Endoscopic ultrasound-guided tissue acquisition for splenic lesions: A systematic review and meta-analysis of diagnostic test accuracy - Xiao Pan; Shu Huang; Peiling Gan; Lei Shi; Huifang Xia; Xinyi Zeng; Han Zhang; Muhan Lü; Xian Zhou; Xiaowei Tang (PLoS ONE, 2022)
Background and aims At present, it is difficult and risky to diagnose splenic lesions by conventional needle biopsy using computed tomography (CT) or ultrasound (US). Endoscopic ultrasound (EUS)-guided tissue acquisition is increasingly being used as a new technique to determine the tissue diagnosis of splenic lesions. Therefore, our goal was to determine the efficacy and safety of EUS-guided tissue acquisition for splenic lesions. Methods We performed a systematic review and meta-analysis to evaluate the pooled sensitivity and specificity of EUS-guided tissue acquisition for the diagnosis of splenic lesions using Metadisc. The Quality Assessment of Diagnostic Accuracy Studies Questionnaire, a quality assessment tool, was used to scrutinize the quality of the studies. Results Six eligible studies between January 2000 and June 2022 were identified, and a total number of 62 patients (aged range from 19 to 84) were enrolled. One patient was excluded because of insufficient specimens. The pooled sensitivity and specificity of included studies were 0.85 [95% confidence interval (CI), 0.73–0.93] and 0.77 (95% CI, 0.46–0.95), respectively. The pooled positive likelihood ratio (LR) was 2.38 (95% CI, 1.24–4.57), the pooled negative LR was 0.31 (95% CI, 0.17–0.55), the pooled diagnostic odds ratio (DOR) was 8.67 (95% CI, 2.80–26.82), the area under the summary receiver operating characteristic (SROC) curve was 0.8100 (Standard Error 0.0813). Conclusion EUS-guided tissue acquisition is a safe technique with high sensitivity in the diagnosis of splenic lesions. However, because of the small sample sizes, more studies with more cases are needed to further validate these results.